Spontaneous spawning in captivity of the first generation hatchery-produced weakfish, Cynoscion squamipinnis (Perciformes: Sciaenidae) - Boza-Abarca, Jorge (2017)
The aim of this study was to evaluate the spontaneous spawning of the first generation of weakfish (Cynoscion squamipinnis) reared in captivity in order to conduct restocking programs and mariculture projects. Juveniles obtained from spontaneous spawning of wild fish caught in the Gulf of Nicoya were reared at the Laboratory of Marine Fish Reproduction and Culture in the Juan Bertoglia Richards Marine Biology Station, Universidad Nacional, Puntarenas, Costa Rica. Fish were kept in 18 t tanks, with constant water exchange (100% per day), at a temperature of 26.73 ± 1.15°C, 32.60 ± 2.69 PSU salinity, and 6.20 ± 0.61 mg/L dissolved oxygen. Every two months croakers were anesthetized and examined for sexual maturity. In January 2011, maturity of one female was confirmed by ovarian biopsies, and oocytes of 0.4-0.6 mm diameter were observed; also fluid semen was obtained from males through abdominal massage. In March 2011, a period of spontaneous spawning began, without any environmental or hormonal stimulation. In total 34 spawns were recorded from March to October 2011, for an average of 85,996 eggs, with a maximum production of 461,000 eggs and a minimum of 4,500 eggs. Fertilization percentage was 10-80%, with an average of 53.09 ± 26.97%. No significant correlations were found between spawns and environmental variables such as temperature, salinity, dissolved oxygen, tides, moon phases and precipitation.